Performance evaluation of drilling medium carbon steel by using Minimum Quantity Lubricant (MQL) [microfilm] - Fakulti Kejuruteraan Mekanikal (2006)
Project Paper (Sarjana Muda) - Universiti Teknologi Malaysia, 2006